Sociolinguistic Features for Author Gender Identification: From Qualitative Evidence to Quantitative Analysis. Issue 1 (2nd January 2017) - Simaki, Vasiliki; Aravantinou, Christina; Mporas, Iosif; Kondyli, Marianna; Megalooikonomou, Vasileios
Abstract: Theoretical and empirical studies prove the strong relationship between social factors and the individual linguistic attitudes. Different social categories, such as gender, age, education, profession and social status, are strongly related with the linguistic diversity of people's everyday spoken and written interaction. In this paper, sociolinguistic studies addressed to gender differentiation are overviewed in order to identify how various linguistic characteristics differ between women and men. Thereafter, it is examined if and how these qualitative features can become quantitative metrics for the task of gender identification from texts on web blogs. The evaluation results showed that the "syntactic complexity", the "tag questions", the "period length", the "adjectives" and the "vocabulary richness" characteristics seem to be significantly distinctive with respect to the author's gender.